Modelagem de sistemas de armazenamento a baterias com aplicação em estudos de estabilidade de frequência em redes com geração fotovoltaica - Gomes, Anny Elena (2019)
[EN] This work describes battery energy storage systems modeling on Simulight, based on the Western Electricity Coordinating Council (WECC) generic models, in order to enable frequency stability studies on power systems with high photovoltaic generation. It focuses on batteries that operate integrated with large-scale photovoltaic power plants, through a centralized control model. It proposes solutions for practical situations on power systems, by different methodologies of load sharing between the photovoltaic power plant and the battery energy storage system when underfrequency events occur. Among these solutions, an adaptive droop method for batteries is proposed and implemented, so that the effects of battery’s discharge is minimized and the load is smoothly transferred to the other generators. The implementations are tested on different power systems, through which the satisfactory performance of the models and usefulness of the proposed methodologies are acknowledged.